تغيرات بعض مؤشرات الدم خلال الحمل في نعاج العواس - جبور زهير إبراهيم; الدقر المعتصم بالله; دمسرخو نسرين (Latakia University Journal -Biological Sciences Series, 2014)
نُفّذ البحث بالتعاون بين جامعة تشرين والهيئة العامة للبحوث العلمية الزراعية في محطة بحوث قرحتا لتحسين الماعز الشامي ومحطة دير الحجر, بهدف وضع جداول للقيم الطبيعية لبعض المؤشرات الدموية والكيميائية في إناث أغنام العواس خلال فترة الحمل تفيد في التنبؤ المسبق لحدوث أي خلل تغذوي أو صحي. واستخدم لهذا الغرض 47 أنثى متقاربة في الوزن والعمر (موسم3 ), أخذت منها عينات دموية كل شهر قبل التلقيح وطيلة فترة الحمل وبعد الولادة, وتم تحليل المؤشرات التالية: الألانين ناقلات الأمين (ALT), الأسباراتات ناقلات الأمين (AST), الألكالين فوسفاتاز (ALP). بيّنت النتائج وجود تغيرات معنوية (0.05P<) بين ازدياد ونقصان في كافة المؤشرات المدروسة طوال فترة الدراسة, مما يدل على تغيّر الحالة الوظيفية للكبدبالارتباط مع مرحلة الحمل. كان المتوسط العام لفعالية الأنظيمات (2.05-26.47), (32.65-181.40), (11.17-79.76) وحدة دولية/لتر لكل من الـALP و AST وALT على التواليطوال فترة الدراسة. This research was done as a collaboration work between Tishreen University and the General Commission for Scientific Agricultural Research in Karahta research station for improvement of Shami goats and Der Al-Hajar station to set tables for normal values of some blood and chemical parameters in Awassi sheep during pregnancy to predict any nutrition or health disorders. Forty seven Awassi ewes in the same age (in the third season) were used for that purpose. Blood sample were collected from all ewes every month of the pregnancy period. Thealanine aminotransferase (ALT),the aspartate aminotransferase (AST), the alkaline phosphatase (ALP), the glucose (Glu) were analyzed. Results indicated the existence of significant changes (P<0.05) between the increase and decrease in all indicators studied throughout The study period, which shows the change in functional status of liver in conjunction with stage of pregnancy.The overall average of the effectiveness of enzymes (2.05-26.47), (32.65-181.40) and (11.17-79.76) U/l for each of the ALP, ALT and AST, respectively, and total concentration of glucose (37,50-95.20 mg/dl) throughout the study period.